Measuring Diagnostic Skills through the Utilization of Cues. (September 2014) - Wiggins, Mark W.
The aim of this paper is to outline a theoretical and empirical case for the role of cue utilization in the cognitive process of diagnosis. Drawing on theories of skill acquisition, the case is made that the utilization of cues represents a critical precursor to the progression toward expertise but that the acquisition and utilization of cues is dependent upon a repertoire of cases and exemplars that have been acquired during the progression from novice to competence. Cases and exemplars form the basis of a mental model from which cues, in the form or feature-event or feature-object relationships, can be identified and retained in memory. The implications of a more sophisticated understanding of the role of cue utilization in skill acquisition will provide the foundation for more effective and more efficient industrial training systems in the future.